Phytomedicines containing Matricaria species for the treatment of skin diseases: A biotechnological approach - dos Santos, Damaris Silva; Barreto, Rosana de Souza Siqueira; Serafini, Mairim Russo; Gouveia, Daniele Nascimento; Marques, Raquel Souza; Nascimento, Laranda de Carvalho; Nascimento, Jéssica de Carvalho; Guimarães, Adriana Gibara (Elsevier, 2019)
Skin diseases have a notable impact on the life of the affected and in their health conditions. In order to allow a more effective and economical treatment for such disorders, new therapeutic approaches have been continuously investigated. Due to its high therapeutic and phytochemical potential, Matricaria species emerges as a pleasant alternative, since it is an important source of bioactive secondary metabolites suitable for the treatment of varied skin diseases. Therefore, this review aimed to catalog inventions that have used Matricaria species as the active component for skin disease treatment in order to assess the status of the technological development of the fitomedicines. For this, a search of patents was performed in four specialized patent database, which have reported the discovery of pharmaceutical bioproducts that used Matricaria species in its composition for skin treatment. Therefore, it is possible to notice that the pharmaceutical industry has driven efforts and investment to produce medicines for the dermatopathies, using species of this genus as an active principle. Besides, a trend of growth has been identified for the last years, which is accompanied by the continuous publication of scientific articles on the subject. It is known that a long journey is traversed between the scientific findings and their applications in the pharmaceutical market, creating the perspective that new Matricaria-based medicines may reach the pharmaceutical market in the coming years.
Keywords: Biotechnology; Matricaria; Skin diseases